Antimicrobial activity of surfactants synthesized by Rhodococcus erythropolis IMV Aс-5017 in the presence of a biological inducer and precursors of phytohormone biosynthesis - Okhmakevych, Anastasiia; Pirog, Tatiana (My University, 2025)
The biological activity of biosurfactants produced by Rhodococcus erythropolis IMV Ac-5017 is strongly influenced by cultivation conditions, particularly by the presence of phytohormone biosynthesis precursors and a yeast inducer in the culture medium. The addition of inactivated Saccharomyces cerevisiae BTM-1 cells promoted the synthesis of biosurfactants with enhanced antimicrobial activity against the phytopathogenic bacteria Clavibacter michiganensis and Agrobacterium tumefaciens. For these biosurfactant preparations, the minimum inhibitory concentrations were 2.4–19.2 times lower than those of surfactants obtained in the absence of the inducer, indicating a substantial enhancement of biological activity resulting from changes in biosynthesis conditions. Біологічна активність поверхнево-активних речовин (ПАР) Rhodococcus erythropolis IMВ Ac-5017 помітно змінюється залежно від умов культивування, зокрема від наявності у середовищі попередників біосинтезу фітогормонів та дріжджового індуктора. Внесення інактивованих клітин Saccharomyces cerevisiae БТМ-1 сприяє синтезу ПАР із підвищеною антимікробною дією щодо фітопатогенних бактерій Clavibacter michiganensis та Agrobacterium tumefaciens. Для таких препаратів зафіксовано зниження мінімальних інгібувальних концентрацій у 2,4–19,2 раза порівняно з поверхнево-активними речовинами, одержаними у середовищі без індуктора, що свідчить про суттєве посилення біологічної активності ПАР за рахунок зміни умов їх біосинтезу.
Keywords: antimicrobial activity; антимікробна активність; inducer; індуктор; tryptophan; триптофан; erythritol; еритритол; phytopathogenic bacteria; фітопатогенні бактерії; кафедра біотехнології і мікробіології